ANALISIS PENERAPAN PEMBELAJARAN MATEMATIKA BERBASIS PMRI PADA SEKOLAH DASAR DI KOTA BANDUNG - Masta Hutajulu; Marchasan Lexbin E.J.R (Jurnal Ilmiah P2M STKIP Siliwangi, 2016)
The research is conducted to observe if Mathematics teacher who use PMRI base consistently apply the characteristic especially to students of grade 4 primary. The  purpose of this research is to give contribution to all Mathematics teachers who apply PMRI. The data collection technique that use is observation method. The results of research are: 1) the application of PMRI in collaborator school (grade 4 primary) is consistent to the characteristics of PMRI. 2) Mathematics teachers who apply PMRI use the method according to the standard.Keyword: Realistic Mathematics Education of Indonesia (PMRI)